PENGARUH KUALITAS WEBSITE DALAM LAYANAN E-KIOS TERHADAP KEPUASAN MASYARAKAT DI KELURAHAN NGINDEN JANGKUNGAN SURABAYA - Ramadhani, Putu Ayu; Radjikan, Radjikan; Zakariya, Zakariya (Universitas 17 Agustus 1945 Surabaya, 2017)
In the current era of information technology, demanding effective and efficient public services along with the diverse needs and wants of everyone. The existence of public services e-Kiosk is one sign of the development of information technology with the aim to improve the quality of service. Thus the authors take the title of Website Quality Influence In e-Kiosk Service Against Satisfaction Society (Urban Nginden Jangkungan Surabaya) because there is still a public complaints over the e-Kiosk machine disorder that sometimes does not work properly. The purpose of this research is to know the effect of simultaneous and partial of website quality dimension that is usability (X1), information quality (X2), and service interaction quality (X3) with community satisfaction (Y) and which is the most dominant influence to public satisfaction. This research uses correlational research with quantitative approach of 100 respondents conducted by accidental sampling sampling technique in Nginden Jangkungan Urban Village and data collection technique through observation, questionnaire, and literature study. The results showed that simultaneously, the three dimensions of website quality affect the satisfaction of the community. Partially, usability and information quality have influence to public satisfaction, while service interaction quality does not have influence to the satisfaction of society and from third dimension of website quality, information quality dominant influence to public satisfaction.Â Key words: quality website, Usability, Information Quality, Service Interaction Quality, and community satisfaction